Experimental Verification of the Flexible Wheels for Planetary Rovers with the Push–Pull Locomotion Function - Qingze He; Daisuke Fujiwara; Kojiro Iizuka (Aerospace)
For push–pull locomotion, it has been confirmed by this research group that the support force of the wheels is enhanced by performing the sinking operation to provide support force. However, the sinking operation is an additional operation used for the rover to travel. Ideally, if the rover can operate without sinking, travel efficiency is improved. On the other hand, flexible wheels are often used for the rover. Due to stress dispersion, these wheels are less likely to damage the ground. Therefore, it would be beneficial if the use of these wheels could improve the travel ability of the push–pull motion. In this study, we focused on whether the use of flexible wheels can avoid subsidence and tested their performance through different parameters.